INCLUDERE: An Immersive Experience that Transforms Perceptions of Inclusion - Peres, Tati; Peres, Fabiana; Nunes, Fátima; Teixeira, João Marcelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Building virtual environments that truly foster empathy is challenging, because designers must deliver persuasive first-person perspective-taking without reinforcing stereotypes, inducing cybersickness, or exceeding the tight thermal envelope of standalone headsets. Although many studies have proposed VR simulations that embody one specific disability—e.g. blindness, wheelchair use, or autism—no prior work, to our knowledge, chains multiple heterogeneous impairments into a single, culturally grounded narrative optimized for untethered mobile VR. INCLUDERE addresses this gap by offering a six-minute journey whose overarching goal is to let visitors inhabit, rather than merely observe, the spatial, sensory and social frictions that shape disabled life in Brazil. The experience unfolds through six metaphor-driven vignettes (autism, dwarfism, visual, motor and hearing impairments, plus an intersectional finale), each pairing a tailored interaction mechanic with stylised volumetric live-action footage that sustains real-time FPS (frames per second) on Meta Quest headsets. This paper makes three contributions. We introduce a design grammar for chaining heterogeneous disability simulations into a coherent empathic arc while mitigating cybersickness and “empathy fatigue”. We detail a content-first technical stack that blends hand-tracking and adaptive vignette masks inside the strict performance envelope of mobile VR. We report a contractor-focused qualitative evaluation—encompassing museum curators, NGO advocates and corporate sponsors—that surfaces operational constraints and ethical sensitivities rarely captured in laboratory studies. Early feedback highlights strong emotional resonance, praises the Libras–caption pairing as a concrete act of inclusivity, and calls for an optional comfort mode to reduce physical fatigue. By weaving multiple embodiments into a single, culturally resonant narrative, INCLUDERE positions VR not as spectacle but as a tool for civic reflection.